PENERAPAN MODEL PEMBELAJARAN SETS (SCIENCE ENVORINTMENT TECHNOLOGY AND SOCIETY) UNTUK MENINGKATKAN PENGUASAAN KONSEP IPA SISWA - Juita Indri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research was initiated by the demands of the 2013 curriculum emphasizing that learning must involve students to be active, while the facts found that the teacher was still the center of learning; as a result, students' creativity and skills were weak and students' mastery of concepts was low. SETS learning model was expected to improve students' mastery of concepts. This research was a classroom action research conducted on students of class IX B MTs Negeri 1 Kuantan Singingi. The number of subjects in this study was 29 students. The instruments were the observation sheet and the student's conceptual mastery test. The results showed that the teacher's action in cycle I was 68% with sufficient category, and it increased to 81% in cycle II with good category. Then, students’ activity in cycle I was 69% with sufficient category and it got to 84% in cycle II with good category. After that, the results of students’ concept mastery test in cycle I obtained an average score of 64.13 with classical completeness of 51.72%. In cycle II, the average score of students’ mastery of concepts was 70.86 with a percentage of classical student completeness of 93.10%. Based on these results, it was concluded that SETS learning model improved students’ mastery of concepts at grade IX B MTS Negeri 1 Kuantan Singingi.